Arthur ainda vive? - Isadora Cristine Martins (Medievalista)
There is a historiographical tradition that connects King Arthur with royal messianism, expressed by the belief that some insular ethnic groups (Cornish, Welsh, and Bretons) had in his return. This hope, known in historiography as “the Breton hope”3, was suggested in some sources during the 12th and 13th centuries, in which chroniclers stated that Arthur was not, in fact, dead for some groups within Great Britain’s territory. Since the 1990s, the discussion about the Breton hope has changed. Virginie Greene questions the pertinence of using the term “messianism” in the Middle Ages and argues that it cannot be used in the same sense as used by historians to refer to Modernity4.In this essay we try to withdraw the analysis from the courtly environments in which they were reproduced, through some selected chronicles, from a History from Below perspective, to understand who are the people waiting for Arthur’s return and whether this hope represents more than a speech constructed by the chroniclers.From a crossing between chronicles and archaeological studies, we try to map cults, traditions, and pilgrimages linked to Arthur that circulated through Great-Britain under the Norman rule. We read the sources observing side references to Arthur and paying attention to the power relations that the chronicles contain.